Assessment of potential toxicity of foodborne fluorescent nanoparticles from roasted pork. Issue 10 (26th November 2019) - Zhao, Xue; Shan, Shihui; Li, Jiaqi; Cao, Lin; Lv, Jing; Tan, Mingqian
Abstract: Foodborne nanoparticles (NPs) refer to the nanostructures generated during food processing, rather than the man-made nano-structural additives that are added to improve the property of food. In this research, discovery of fluorescent NPs in roasted pork was reported at different temperature of 180, 230, and 280 °C. The size of the pork NPs was in the range of 5.93–7.49 nm. The FTIR and XPS analysis showed that the NPs are made up of graphitic carbon (sp2) and carbon defects (sp3), with abundant hydroxyl and carbonyl groups on the surface. The Ussing chamber test clearly showed the pork NPs had permeability passing through intestine. Significant fluorescence quenching of NPs was observed in the digestion in vitro . The bio-distribution of NPs in mice indicated that they obviously presented in liver, kidney and testis, even crossed the blood-brain barrier, entering into the brain. The oral administration of pork NPs at a dose of 2 g/kg mouse body weight did not caused obvious toxicity in BALB/c mice. However, significant influence of the NP exposure was observed on locomotion behaviors and lifespans in wild type Caenorhabditis elegans .